Jesus' Prayer as a Contemplative Practice: Inner Transformation and Encounter with the Divine - Sapatandekan, Imel Yovita; Hendi, Hendi; Halim, Sugianto; Handoko, Yusuf Slamet (STT Transformasi Indonesia Manado, 2025)
This article delves into the profound significance of the Jesus Prayer, as presented by Kallistos Ware, and its role in nurturing spiritual growth and leading believers toward a deeper union with God. By employing a qualitative literature review, this study engages with Ware’s theological perspectives and other relevant insights. The findings highlight how this simple yet powerful prayer—“Lord Jesus Christ, Son of God, have mercy on me, a sinner”—serves as a tool for believers to transcend distractions, cultivate inner peace, and center their hearts on Christ. The research affirms that the Jesus Prayer is not just a repetitive phrase but a pathway to transformation, offering believers a way to experience God’s grace in their everyday lives.